Autoimmune thyroiditis in different age groups and subjects of reproductive age in Adzhariya population - N. G. Tchelidze; S. Z. Glonti; D. Sh. Baratashvili; N. O. Kedelidze; J. Yu. Ungiadze; I. I. Nakashidze (IRBIS LLC, 2022)
Introduction. Autoimmune thyroiditis (AIT) is the most prevalent among the autoimmune pathologies and multifactorial thyroid diseases; accordingly, remaining a pressing issue for investigation.Aim: to study AIT profile in different age groups of the female population in the western region of Georgia - Adzhariya.Materials and Methods. A prospective comparative study in parallel groups was carried out. There were examined 405 samples of venous blood obtained at «Health» Clinic from women of two groups: group 1 - 159 patients with AIT, group 2 (control) - 246 women without AIT. Blood samples were collected between the years 2017 and 2020. There were analyzed serum antibodies against thyroperoxidase (TPOAb), thyroid stimulating hormone (TSH) as well as level of free thyroxine (FT4) by using enzyme immunoassay.Results. Patients with AIT from different age groups vs. control group were found to have decreased level of FT4, but increased amount of TSH and TPOAb. At the reproductive age (18-45 years), a significant increase in the level of TSH was found (6.12 times) compared with the control group (p < 0.0001). The level of FT4 and TSH in AIT women aged 51 to 60 years was 0.7880 ± 0.3584 ng/ml and 4.754 ± 2.433 U/ml that significantly differed from those in the control group - 1.314 ± 0.4044 ng/ml (p < 0.0001) and 2.276 ± 1.409 U/ml (p < 0.0001), respectively.Conclusion. AIT occurs in women of all age groups, but is more common in women aged 51 to 60 years. In a number of cases, TPOAb was detected in the control group, which, apparently, is associated with increased intake of dietary iodized salt since 2005 in Georgia (the adoption of the law on universal salt iodization). A significant increase in the level of TSH, in AIT women aged 18-45 years, strongly suggests to perform diagnostics of and screening for AIT not only in females of menopausal period, but also in reproductive age.